Normative values of resting heart rate variability in young male contact sport athletes: Reference values for the assessment and treatment of concussion - Ziadia, H.; Sassi, I.; Trudeau, F.; Fait, P. (Frontiers in Sports and Active Living, 2023)
Objective: The objective of this study was to identify the main determinants of heart rate variability (HRV) in male athletes aged 14 to 21 years who practice competitive contact sports and to integrate these determinants with the aim of defining normative values of short-term HRV in the time and frequency domains.